Study on the Evolution of Urban Green Space Patterns in Zhengzhou from 2000 to 2024 - Kong, Xuekai (International Journal of Natural Resources and Environmental Studies, 2026)
Urban green spaces are an essential component of urban ecosystems, and their spatiotemporal evolution and landscape structural changes have a significant impact on urban ecological functions. This study focuses on the central urban area of Zhengzhou and utilizes long-term Landsat remote sensing imagery data from 2000 to 2024. A combination of methods, including urban green space interpretation, buffer zone analysis, standard deviation ellipse, and landscape pattern indices, is applied to systematically analyze the spatiotemporal evolution characteristics and landscape pattern changes of urban green spaces. The results show that: (1) The scale of urban green spaces has continuously expanded during the study period, with the total green space area increasing from 115.79 km² to 417.00 km², and the green space coverage rate surpassing 40%. The expansion process demonstrates a distinct phase progression, shifting from early-stage peripheral aggregation to a simultaneous "infill and outward expansion" approach. (2) The coverage of green space services has evolved from contraction to balance. The 300-meter buffer zone analysis indicates a significant improvement in green space accessibility after 2020, with near-complete coverage of the central urban area by 2024. (3) The spatial center of gravity of green spaces has generally maintained a "northwest-southeast" axial alignment, with a migration trend converging from the periphery towards the center. (4) Landscape pattern analysis shows that the increase in the number and density of patches has led to a rise in micro-level fragmentation. However, the largest patch index and connectivity index have remained at relatively high levels, maintaining a stable overall network structure for the urban green space system. The findings provide valuable insights for optimizing urban green space systems in rapidly urbanizing areas.